Effect of milk feeding management on performance of Beetal kids under stall-fed conditions (Indian Journal of Animal Production and Management, 2017)
To estimate the quantity and frequency of milk intake for optimum performance of Beetal kids during first  3 months of age, 36 newly born kids were randomly distributed into three groups i.e. T0, T1 and T2. The  quantity of milk offered to each kid was 1/10th, 1/8th and 1/6th of their body weight during 1st month;1/12th,  1/10th& 1/8th during 2nd month and 1/14th, 1/12th& 1/10th during 3rd month in T0, T1 and T2 groups, respectively.  Each group was further subdivided into 3 sub-groups (n=4 each) based on milk feeding frequency i.e. 2,  3 and 4 times per day as T02, T03, T04; T12, T13, T14 and T22, T23, T24, respectively. Creep feed and seasonal  green fodder were offered from 15th days onwards to all the kids. Kids were observed for various parameters  such as daily milk yield, feed intake, body weight gain, feed conversion ratio (FCR) and health status. Milk  as well as concentrate feed intake was significantly (P
Keywords: Beetal kids; Feed consevation ratio; Growth rate